2019
DOI: 10.1111/are.14194
|View full text |Cite
|
Sign up to set email alerts
|

Light intensity affects the survival and growth of matrinxã larvae, Brycon amazonicus (Spix & Agassiz, 1829)

Abstract: We evaluated the effect of light intensity on survival rate and zootechnical performance in matrinxã larvae (Brycon amazonicus) that is an important species for fish farming in the Amazon region. For this, the larvae were submitted to three experimental stages: Stage I-10-72 hr after hatching (HAH), Stage II-72-168 HAH and Stage III-168-288 HAH. The animals were submitted to three treatments of different light intensities: low (±20 lx), intermediate (±200 lx) and high (±2,000 lx). The low light intensity incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…Furthermore, extended photoperiods [i.e., continuous 24 hr light (24 hr light/0 hr dark) or 18 hr light/6 hr dark] have improved larval growth and performance for a number of species, including (among others) rabbitfish, Siganus guttatus (Duray & Kohno, 1988), Atlantic cod, Gadus morhua (Puvanendran & Brown, 2002), snapper, Pagrus auratus (Fielder, Bardsley, Allan, & Pankhurst, 2002), obscure puffer, Takifugu obscurus (Shi, Zhang, Zhu, & Liu, 2010) and Pacific bluefin tuna, Thunnus orientalis (Kurata, Tamura, Honryo, Ishibashi, & Sawada, 2017). On the contrary, other studies have shown that photoperiod has no impact (Blanco et al, 2017;Downing & Litvak, 2000), while negative effects have also been observed where larvae exposed to long daylight photoperiods or high light intensity (Politis, Butts, & Tomkiewicz, 2014) had impaired development (Cañavate, Zerolo, & Fernández-Díaz, 2006), enhanced aggressive behaviour (Lopes, Villacorta-Correa, & Carvalho, 2018;Muller, Villacorta-Correa, & Carvalho, 2019;Vallés & Estévez, 2013), or compromised foraging abilities (Puvanendran & Brown, 2002). For example, longer photoperiods have impaired swim bladder inflation and has lead to skeletal deformities in European sea bass larvae (Villamizar et al, 2009) and reduced development and survival of offspring in European eel, Anguilla Anguilla (Politis et al, 2014).…”
mentioning
confidence: 99%
“…Furthermore, extended photoperiods [i.e., continuous 24 hr light (24 hr light/0 hr dark) or 18 hr light/6 hr dark] have improved larval growth and performance for a number of species, including (among others) rabbitfish, Siganus guttatus (Duray & Kohno, 1988), Atlantic cod, Gadus morhua (Puvanendran & Brown, 2002), snapper, Pagrus auratus (Fielder, Bardsley, Allan, & Pankhurst, 2002), obscure puffer, Takifugu obscurus (Shi, Zhang, Zhu, & Liu, 2010) and Pacific bluefin tuna, Thunnus orientalis (Kurata, Tamura, Honryo, Ishibashi, & Sawada, 2017). On the contrary, other studies have shown that photoperiod has no impact (Blanco et al, 2017;Downing & Litvak, 2000), while negative effects have also been observed where larvae exposed to long daylight photoperiods or high light intensity (Politis, Butts, & Tomkiewicz, 2014) had impaired development (Cañavate, Zerolo, & Fernández-Díaz, 2006), enhanced aggressive behaviour (Lopes, Villacorta-Correa, & Carvalho, 2018;Muller, Villacorta-Correa, & Carvalho, 2019;Vallés & Estévez, 2013), or compromised foraging abilities (Puvanendran & Brown, 2002). For example, longer photoperiods have impaired swim bladder inflation and has lead to skeletal deformities in European sea bass larvae (Villamizar et al, 2009) and reduced development and survival of offspring in European eel, Anguilla Anguilla (Politis et al, 2014).…”
mentioning
confidence: 99%
“…According to Hecht and Pienaar (1993), turbid waters simulate conditions of low light and greater availability of refuge, which ends up increasing the survival of the larvae. Studies that employed the manipulation of light intensity in the larviculture of B. amazonicus showed that at low intensity, larvae with 24, 48, 72, 120 and 240 HAH, showed an increase in their survival rate due to the reduction in the display of aggressive interactions in these periods (Lopes, Villacorta-Correa & Carvalho, 2018;Muller, Villacorta-Correa & Carvalho, 2019). In addition, the turbid waters provide an effective shelter due to the suspended solids, which facilitate hiding by the larvae (Maes et al, 1998;Snickars, Sandstrom & Mattila, 2004;Engström-Öst, Karjalainen & Viitasalo, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Brycon amazonicus is noted for being a fish of economic importance and has potential in aquaculture in Brazil and other South American countries (Muller, Villacorta-Correa & Carvalho, 2019) due to it being well accepted in the consumer market, and for having good growth performance (Zaniboni-Filho, Reynalte-Tataje & Weingartner, 2006;Gomes & Urbinati, 2010). However, one of the main difficulties for large-scale production is the low survival rate due to its aggressive behavior and cannibalism (Carvalho et al, 2018), which can result in more than 90% mortality during larviculture (Bernardino et al, 1993;Romagosa et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…At first, the size of the larvae in different light modes did not differ from each other. However, 288 h post-hatching, high light intensity (2000 lx) significantly increased the size and survival of the larvae (Muller et al, 2019). Nuñez et al (2008) contained Pseudoplatystoma fasciatum catfish larvae in 60-L tanks at different lighting intensities.…”
Section: Growthmentioning
confidence: 99%
“…At first, the size of the larvae in different light modes did not differ from each other. However, 288 h post‐hatching, high light intensity (2000 lx) significantly increased the size and survival of the larvae (Muller et al, 2019).…”
Section: Growthmentioning
confidence: 99%